A Systematic Review of Caregiver Interventions in Infancy to Enable Responsive Caregiving and Secure Attachment in Low and Middle-Income Countries - Gilmour, Kirsty A (Division of Public Health, 2019)
The first 1000 days is recognised as the most sensitive period of development of an individual’s life. Infants in low and middle-income countries face significant risks to their development during this period. Research confirms that having a responsive, caring relationship between the infant and caregiver is a considerable protective factor for infants, and results in better longterm outcomes in cognition, language, academic achievement, social skills and behaviour. The aim of this review was to systematically examine the literature to identify interventions in low and middle-income settings that influence infant-caregiver responsivity and attachment and explore the characteristics of the interventions that contribute to its efficacy. Ten electronic databases were searched (Pubmed, Scopus, PsycINFO, PsycARTICLES, Africa-Wide, CINAHL, Health Source, ERIC, SocINDEX & Cochrane Library), as well as hand searching relevant reference lists for published articles in the English language from 1969-2018. A total of 11 765 studies were identified through the search strategy and 24 studies were included in the review. The included studies were critically appraised and then coded descriptively to enable a narrative synthesis of findings. Studies were from low and middle-income countries in Africa, Asia, Europe and South America and consisted predominantly of randomized control trials, but also quasi-experimental studies and a single cohort and qualitative study were included. All but two studies found positive effects on responsivity, attachment or both. For ten of the studies this effect was significant. The findings suggest implementing individual or group interventions in LMICS has a positive effect on caregiver-infant relationships and can be delivered successfully by trained non-professional staff.